2009
DOI: 10.1002/er.1607
|View full text |Cite
|
Sign up to set email alerts
|

Review of near-field thermal radiation and its application to energy conversion

Abstract: SUMMARYUnderstanding energy transfer via near-field thermal radiation is critical for the future advances of nanotechnology. Evanescent waves and photon tunneling are responsible for the near-field energy transfer being several orders of magnitude greater than that between two blackbodies. The enhanced energy transfer may be used for improving the performance of energy conversion devices, developing novel nanofabrication techniques, and imaging nanostructures with higher spatial resolution. Near-field heat tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
363
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(382 citation statements)
references
References 62 publications
3
363
3
1
Order By: Relevance
“…As one of the fundamental modes of heat transfer, radiative heat transfer plays an important role in a wide spectrum of applications from energy harvesting to thermal management [1][2][3][4][5]. In the far field, the maximum radiative heat transfer rate between two objects is restricted by the black-body limit.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the fundamental modes of heat transfer, radiative heat transfer plays an important role in a wide spectrum of applications from energy harvesting to thermal management [1][2][3][4][5]. In the far field, the maximum radiative heat transfer rate between two objects is restricted by the black-body limit.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews can be found in Refs. [15][16][17][18].The first attempts to measure a heat flux between metallic surfaces at room temperature and micrometric distances have proved to be inconclusive [19,20]. Experiments in the nanometric regime have clearly demonstrated the transfer enhancement [21,22].…”
mentioning
confidence: 99%
“…The near-field radiative heat flux between two semi-infinite homogeneous media at temperatures of T 1 and T 2 (T 1 > T 2 ) can be calculated with fluctuational electrodynamics by [9]:…”
Section: Incorporated With Uniaxial Wave Propagationmentioning
confidence: 99%
“…In particular, the near-field enhancement could be orders of magnitude with the excitation of surface plasmon/phonon polaritons (SPP/SPhP) across the nanometer vacuum gaps [8][9][10][11]; however, it usually requires identical or similar materials for the emitter and receiver to achieve the best coupling effect and thereby maximum heat flux enhancement.…”
Section: Introductionmentioning
confidence: 99%